2014
DOI: 10.1371/journal.pone.0098782
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Postoperative Mortality in Liver Transplantation in the Era of MELD-Based Liver Allocation: A Multivariate Analysis

Abstract: Background and AimsLiver transplantation is the only curative treatment for end-stage liver disease. While waiting list mortality can be predicted by the MELD-score, reliable scoring systems for the postoperative period do not exist. This study's objective was to identify risk factors that contribute to postoperative mortality.MethodsBetween December 2006 and March 2011, 429 patients underwent liver transplantation in our department. Risk factors for postoperative mortality in 266 consecutive liver transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 58 publications
5
39
0
Order By: Relevance
“…34 Finally, as in the case of hepatitis C and some other liver conditions, we observed a genderbased difference in post-transplant outcomes. 35 In the MELD era, our results agree with those of Bruns et al, 36 who found that a female donor was a strong and independent risk factor for 90-day post-LT mortality. The impact of donor gender on outcome has also been studied, but it is still necessary to clarify whether this is related to donor quality rather than donor gender per se, or a gender mismatch that actually impacts post-transplant outcome.…”
Section: Discussionsupporting
confidence: 91%
“…34 Finally, as in the case of hepatitis C and some other liver conditions, we observed a genderbased difference in post-transplant outcomes. 35 In the MELD era, our results agree with those of Bruns et al, 36 who found that a female donor was a strong and independent risk factor for 90-day post-LT mortality. The impact of donor gender on outcome has also been studied, but it is still necessary to clarify whether this is related to donor quality rather than donor gender per se, or a gender mismatch that actually impacts post-transplant outcome.…”
Section: Discussionsupporting
confidence: 91%
“…By the end of 2012, data from the China Liver Transplant Registry, the national scientific registration system of liver transplantation in China, indicated that 23 560 patients had undergone liver transplantation . With developments in surgical techniques for liver transplantation, optimization of immunosuppressive regimens, and improvements in monitoring during the perioperative period, the incidence of postoperative acute rejection (AR) and other short‐term postoperative complications has been reduced considerably . Thus, short‐term survival has increased gradually.…”
Section: Introductionmentioning
confidence: 99%
“…3 With developments in surgical techniques for liver transplantation, optimization of immunosuppressive regimens, and improvements in monitoring during the perioperative period, the incidence of postoperative acute rejection (AR) and other short-term postoperative complications has been reduced considerably. 4 Thus, short-term survival has increased gradually. Nonetheless, long-term complications and quality of life after liver transplantation are attracting increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, only one-third of liver graft recipients were female [8]. Current data determines a greater 90-day mortality for women with high MELD scores in Germany; in contrast, some studies showed a better outcome for female patients overall [8,15,33,34]. It is suspected that women are allocated for smaller and older organs associated with worse graft function, which does not affect survival [15,35].…”
Section: Liver Transplantationmentioning
confidence: 99%